Método de barras como estrategia didáctica para el fortalecimiento de la competencia matemática de resolución de problemas en docentes de grado 5º (2018)
The purpose of the research was to reflect on the implementation of the bar method as a teaching didactic strategy for the strengthening of mathematical problem solving skills in the 5th grade developed by the John F. Kennedy primary educational institution, under the guidelines of education administrators (rectors and coordinators) and classroom teachers of the Magdalena Foundation Municipality of Colombia, through the contributions of Zúñiga G (2013), Serres (2007), Hinojosa (2012), MEN (2002), among others. The research was considered analytical under the feasible project approach with experimental design of transactional field. For this, a population formed by a group of participants was selected, constituted by 2 directors (rectors and coordinators), and six (6) secondary school teachers, that is, eight (8) subjects, whom applied to provide information through the use three instruments of single version constituted by twenty (20) questions with alternatives of open answers, which were interpreted and categorized by criteria of importance or incidence in the case study. It was validated in its content by 3 experts with an acceptable reliability. Among the results, it was identified that the bar method dimension for the resolution of mathematical problems in grade 5 has a good application in the John F. Kennedy institution of the Fundacion Municipality of Magdalena-Colombia with a preponderance in the shared educational management and individual participation among the managers, principals, coordinators and teachers, with a moderate application of strategy innovation by teachers. The didactic strategies of training in design and application of workshops and method of project are considered by the director, and coordinators as the highest applicability and acceptance in student learning. It was determined that the orientation of the PEI in the John F. Kennedy Departmental educational institution of the Municipality of Fundacion, Magdalena of Colombia, is always carried out from the traditional conception with productive component. Theoretical-practical guidelines on pedagogical innovation were proposed in the implementation of the bar method as a pedagogical strategy for the strengthening of mathematical skills and competences in teachers and students based on the execution of teaching didactic strategies.